Pengaruh Latihan Bench Dip Terhadap Kemampuan Passing Bola Basket Pada SMAN 1 Narmada Tahun 2020 - Andi Irawan; Dadang Warta Chandra Wira Kusuma; Nurtajudin Nurtajudin (Universitas Pendidikan Mandalika, 2021)
The problem with this research is that the students' low shooting results are caused by their passing and shooting abilities that are still not optimal. This can be seen when students throw and catch, passing the ball often does not reach the given friend, deep passing is the key to the basketball game. The purpose of this study is to examine the significance of different samples with the formulation of the problem posed is to find out whether there is an effect of bench dip training on basketball passing abilities at SMAN 1 Narmada in 2020